Recent progress on lanthanide scintillators for soft X‐ray‐triggered bioimaging and deep‐tissue theranostics. Issue 4 (20th March 2021) - Jiang, Mingyang; Deng, Zhiming; Zeng, Songjun; Hao, Jianhua
Abstract: Lanthanide scintillators capable of converting the absorbed X‐ray photon energy to ultraviolet (UV) or visible light, are emerged as promising nanoprobes for multifunctional diagnosis and deep‐tissue antitumor therapy such as X‐ray‐excited fluorescence (XEF) imaging, X‐ray‐triggered photodynamic therapy (X‐PDT), and soft X‐ray‐activated NO gas therapy. Such biomedical tools have the potential to overcome the major challenge of the depth barrier suffered by traditional optics. Recently, various lanthanide scintillators have been designed for diagnosis and therapy of deep‐seated tumors. This minireview presents an overview of recent progress on the lanthanide‐based scintillators and illustration of the potential challenges and future development. Abstract : Lanthanide scintillators capable of converting the absorbed X‐ray photon energy to ultra‐violet (UV) or visible light, are emerged as promising nanoprobes for multifunctional diagnosis and deep‐tissue antitumor therapy such as X‐ray‐excited fluorescence (XEF) imaging, X‐ray‐triggered photodynamic therapy (X‐PDT), and soft X‐ray‐activated NO gas therapy. This mini‐review presents an overview of recent progress on the lanthanide‐based scintillators and illustration of the potential challenges and future development.